How Boston Played Sport, Recreation, and Community, 1865-1915 - Hardy, Stephen, 1948-; Herlihy, Mark; Project Muse.; Project Muse. (2019)
How Boston Played is a double delight. It chronicles the birth of Boston sports from early Redstockings games and college rowing regattas, to the exploits of the "Boston Strong Boy," John L. Sullivan. Looking beyond just sporting events, though, it seeks to uncover the sources of the mania for recreation that swept the Hub following the Civil War. As How Boston Played illustrates, the rise of sport is firmly entwined in both the city's development and, more importantly, in a people's search for community. Originally published by Northeastern University Press in 1982. With a new foreword by Mark Herlihy.
The text of this book is licensed under a Creative Commons Attribution-NonCommercial-No derivatives 4.0 International License
Open access edition supported by the National Endowment for the Humanities / Andrew W. Mellon Foundation Humanities Open Book Program.
Reprint of 1982 edition, with new foreword.
Includes bibliographical references (pages [250]-264) and index.
Description based on print version record.
Keywords: Sports; Social conditions; Sports -- Massachusetts -- Boston -- History; Massachusetts -- Boston; Boston (Mass.) -- Social conditions; History; Electronic books; Electronic books